Event-related states in secondary predication - Bosque, Ignacio (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2022)
Analyses of secondary predication based on the aspectual properties of predicative complements are almost standard today. This paper shows that these approaches are not restrictive enough and make a large number of incorrect predictions. It also shows that the meaning of the main (or primary) predicate is essential to restrict the secondary one. Throughout the text, a pragmatically based analysis of the necessary restrictions is compared with one grounded on semantic paradigms, and several examples are proposed of how the latter may be articulated and developed. Event-related states in secondary predication are shown to be necessary, and are claimed to follow from a series if fine-grained semantic notions crucially related to the meaning of the primary verb.